Effect of Priming on Microtubers Sprouting and Physiological Storage Attributes of Potato - Sadawarti, M.; Pandey, K. K.; Samadhiya, R. K.; Singh, R. K.; Singh, Y. P.; Singh, S. P.; Roy, S. (Indian Journal of Hill Farming, 2018)
An experiment was conducted at ICAR-Central Potato Research Station, Gwalior (MP) during 2012-13.Ten microtubers of three varieties viz. Kufri Chandramukhi, Kufri Lauvkar and Kufri Sindhuri were primed with total seven treatments for 10 minutes include water control (hydropriming) and fungicide mancozeb @1% and five bioagents viz B-5 (Bacillus substallis) @ 0.8%, Trichoderma viridie @ 1%, Trichoderma harzanium @ 1%, Aspergillus niger @1% and Phosphorous solubilizing bacteria @1% at 10 days interval up to 60 days (total 7 dates) and stored at ambient temperature. At the end of storage period of 70 days Kufri Lauvkar recorded significantly higher physiological loss in weight (0.88g and 57.26%) over other two cultivars, highest tuber sprouting was recorded in Kufri Sindhuri (91.25%) over other varieties and tubers rottage was significantly higher in in Kufri Lauvkar (30%) over Kufri Chandramukhi (17%), Kufri Sindhuri (11%). Among priming treatments, significantly higher Physiological weight loss was observed in B. substalis @ 0.8% (50.90%) and higher sprouting in control (55.56%) and B-5 (52.22%) over other priming treatments. Significantly higher microtubers were rotted in all the priming treatments over control (12.22%) and T. harzanium @1% (14.44%). Priming with B-5 (B. substallis) @ 0.8% in Kufri Sindhuri resulted in higher sprouting. Less physiological weight loss but higher rottage percent was observed in Kufri Sindhuri during storage at ambient temperature.